Improving referring physicians' understanding of electromyography reports when qualifying radiculopathies: A need for standardized terminology. Issue 1 (22nd November 2013) - Mauricio, Elizabeth A.; Dimberg, Elliot L.; Kennelly, Kathleen D.; Rubin, Devon I.
ABSTRACT Electromyographic (EMG) reporting of radiculopathies is not standardized, and the terminology used in reports can be misinterpreted by referring physicians. Physicians who refer patients for EMG studies at the Mayo Clinic were surveyed about their understanding of 6 different EMG interpretations of an S1 radiculopathy. Of 45 responders, the terms "acute, active, " "chronic, inactive, " and "old" were interpreted consistently by 95%, 98%, and 84% of responders, respectively. Physicians had the most difficulty understanding the meaning of "chronic" in isolation, "chronic, active, " or "old with uncompensated denervation." These findings suggest a need to educate referring physicians on the meaning of the terms used in EMG reports and to develop standard guidelines for qualifying radiculopathies. Based on our observations, guidelines for the reporting of radiculopathies have been adopted in the Mayo Clinic Florida EMG laboratory. Muscle Nerve49: 129–130, 2014